2017
DOI: 10.1155/2017/1068982
|View full text |Cite
|
Sign up to set email alerts
|

Periapical Status and Quality of Root Canal Fillings in a Moroccan Subpopulation

Abstract: Aim The aim of the study was to assess the prevalence of apical periodontitis (AP) and quality of root canal fillings in an adult Moroccan subpopulation. Methods In the study 508 patients were included, attending the Conservative Dentistry Clinic at the Faculty of Dentistry of Casablanca. 508 panoramic and 709 periapical radiographs were observed. The periapical status of all teeth (with the exception of third molars) was examined according to Ørstavik's periapical index. The statistical analysis was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
1
7
1
Order By: Relevance
“…However, this percentage is lower compared with the results from Mukhaimer et al ( 21 ) in Palestine (15.1%) and Oginni et al ( 45 ) in Nigeria (14.4.%), but higher than the proportions documented by Skudutyte-Rysstad & Eriksen ( 20 ) in Norway (1.1%) and Ureyen Kaya et al ( 36 ) in Turkey (1.2%). Additionally, the results of the present study showed that the prevalence of periapical lesions in root canal filled teeth was 54.0%, which is a lower percentage when compared to the one from Morocco (66.8%) ( 46 ) and Spain (64.5%) ( 8 ) but considerably higher than the reported prevalence in Finland (15.3%) ( 22 ). Table 6 and Figure 3 summarize the previous literature regarding the prevalence of periapical lesions ( 7 , 9 , 10 , 15 , 16 , 20 - 25 , 36 - 88 ).…”
Section: Discussioncontrasting
confidence: 57%
“…However, this percentage is lower compared with the results from Mukhaimer et al ( 21 ) in Palestine (15.1%) and Oginni et al ( 45 ) in Nigeria (14.4.%), but higher than the proportions documented by Skudutyte-Rysstad & Eriksen ( 20 ) in Norway (1.1%) and Ureyen Kaya et al ( 36 ) in Turkey (1.2%). Additionally, the results of the present study showed that the prevalence of periapical lesions in root canal filled teeth was 54.0%, which is a lower percentage when compared to the one from Morocco (66.8%) ( 46 ) and Spain (64.5%) ( 8 ) but considerably higher than the reported prevalence in Finland (15.3%) ( 22 ). Table 6 and Figure 3 summarize the previous literature regarding the prevalence of periapical lesions ( 7 , 9 , 10 , 15 , 16 , 20 - 25 , 36 - 88 ).…”
Section: Discussioncontrasting
confidence: 57%
“…The current study aimed to investigate risk factors associated to apical periodontitis and to highlight the combined risk of AP assigned to proximal restorations and gingival status in endodontically treated teeth not investigated previously. Epidemiological studies in different populations often reveal a high rate of AP associated with root lled teeth [23][24][25]. The results of the present study indicate that (72.1%) of the root lled teeth had AP, this gure is in the range of those found in previous studies [26][27][28][29], and higher than other reports [30].…”
Section: Discussionsupporting
confidence: 52%
“…El Merini et al recorded in their study AP in 91. 5% of endodontically treated teeth with inadequate root canal treatment, and AP in their study was significantly associated with insufficient root canal fillings (P < 0.05) [ 5 ]. Moreover, in a Meta-analysis of previous cross-sectional studies published between 2012 and 2020, Jakovljevich et al, had shown a significant higher prevalence of AP in treated teeth with inadequate root canal treatment (OR = 4.65; 95% CI 2.75–7.84; p < 0.00001), and a significant higher prevalence of AP in ETT with poor coronal restoration (OR = 1.54; 95% CI 1.16–2.05, p = 0.003) [ 9 ], these findings are all in accordance with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Apical periodontitis (AP) is an inflammatory disease of periapical tissues and develops as a host’s immune response to the presence of microorganisms and their irritants within the root canal system [ 1 ]. In most of the cases, AP is a direct consequence of dental caries [ 2 ], nevertheless several authors have reported that AP is more prevalent in endodontically treated teeth (ETT) [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation